Clonal Evolution and Timing of Metastatic Colorectal Cancer - Siraj, Sarah (Cancers (Basel), 2020)
SIMPLE SUMMARY: Half of all colorectal cancer (CRC) patients develop metastasis, despite current management. The aim of this study was to help guide precision medicine in metastatic CRC patients, by performing genomic characterisation of primary CRC and metastatic tumours, and revealing the effects of therapy on the metastatic process. We confirmed common ancestry between paired primary CRC and metastatic tumours, with most metastases seemingly having disseminated late (after acquiring most genomic diversity) from their corresponding primary tumour, via either a single clone (monoclonal spread) or multiple clones (polyclonal spread). Treatment prompted the selection for distinct resistant clones, through monoclonal seeding to distant metastatic sites. Overall, this study supports the importance of early clinical detection and surgical removal of the CRC tumour, whilst further highlighting the challenges for treating and managing metastatic CRC with increased intratumour heterogeneity (either due to early dissemination or metastatic spread through multiple clones) and the underlying risk of future therapeutic resistance in treated patients. ABSTRACT: Colorectal cancer (CRC) is the third most frequently diagnosed cancer worldwide, where ~50% of patients develop metastasis, despite current improved management. Genomic characterisation of metastatic CRC, and elucidating the effects of therapy on the metastatic process, are essential to help guide precision medicine. Multi-region whole-exome sequencing was performed on 191 sampled tumour regions of patient-matched therapy-naïve and treated CRC primary tumours (n = 92 tumour regions) and metastases (n = 99 tumour regions), in 30 patients. Somatic variants were analysed to define the origin, composition, and timing of seeding in the metastatic progression of therapy-naïve and treated metastatic CRC. High concordance, with few genomic differences, was observed between primary CRC and metastases. Most cases supported a late dissemination model, via either monoclonal or polyclonal seeding. Polyclonal seeding appeared more common in therapy-naïve metastases than in treated metastases. Whereby, treatment prompted for the selection of distinct resistant clones, through monoclonal seeding to distant metastatic sites. Overall, this study reinforces the importance of early clinical detection and surgical excision of the CRC tumour, whilst further highlighting the clinical challenges for metastatic CRC with increased intratumour heterogeneity (either due to early dissemination or polyclonal metastatic spread) and the underlying risk of future therapeutic resistance in treated patients.